Differential Effects of an Alpha-2 Agonist on Wakefulness and Paradoxical Sleep in The Rat: A Polygraphic and Biochemical Approach - Z. de Saint Hilaire; F. Karege; J.-M. Gaillard; R. Blois (Behavioural Neurology)
The purpose of this experiment was to determine the sensitivity of wakefulness and paradoxical sleep to the α2-agonist, c1onidine. The drug inhibited both wakefulness and paradoxical sleep but the smallest dose necessary to inhibit wakefulness was 64 times larger than the smallest dose inhibiting paradoxical sleep. The effect on paradoxical sleep was inhibitory for all the clonidine doses but wakefulness was enhanced transiently after the four largest doses used. The time between injection and maximum wakefulness enhancement was highly correlated with the dose of c1onidine. The brain level measured after these four different doses at the moment of maximum wakefulness enhancement was the same, suggesting that this effect occurred only when a critical concentration of the drug was attained in the brain and not when the concentration was higher or lower. These data suggest that different α2-adrenoceptors are involved in these two states of vigilance or, alternatively, that their sensitivity is modulated physiologically. In addition, a sensitivity imbalance between different α2-adrenoceptors may exist in wakefulness but not in paradoxical sleep.